Integrated Existential Education Model for Juvenile Justice Reform: A Human Rights-Based Approach in Indonesia - Lilik Sujandi; Suwito Eko Pramono; Inaya Sari Melati; Ridwan Arifin; Valerio Sebastian; Syaiful Amin (TRUNOJOYO LAW REVIEW, 2026)
Juvenile justice systems worldwide face persistent challenges in balancing accountability, rehabilitation, and the protection of children’s rights. Traditional punitive approaches often fail to address the underlying existential and psychosocial needs of adolescents, contributing to high recidivism rates and social marginalization. This paper proposes an Integrated Existential Education Model as a transformative framework for juvenile justice reform within the context of international human rights, with a case study conducted at the Lembaga Pembinaan Khusus Anak Kelas I (LPKA) Kutoarjo, Central Java, Indonesia. Drawing on existential psychology, the model emphasizes self-awareness, personal responsibility, and meaning-making, empowering adolescents to reflect on their life choices and develop authentic identities. It integrates human rights education and restorative practices to foster empathy, respect for others, and adherence to legal and ethical norms. Methodologically, the study employs a qualitative approach, including interviews with adolescents, educators, and staff, as well as analysis of international child rights frameworks, to examine the feasibility and potential impact of the model. The findings suggest that implementing existential education within juvenile rehabilitation programs can enhance psychological resilience, reduce recidivism, and promote social reintegration while ensuring compliance with global human rights standards. This integrated approach offers a practical, rights-based strategy for policymakers and practitioners in Indonesia and beyond.